2008
DOI: 10.1002/ps.1662
|View full text |Cite
|
Sign up to set email alerts
|

QoI resistance emerged independently at least 4 times in European populations of Mycosphaerella graminicola

Abstract: This study demonstrated that recurring mutations independently introduced the QoI resistance allele into different genetic and geographic backgrounds. The resistant haplotypes then increased in frequency owing to the strong fungicide selection and spread eastward through wind dispersal of ascospores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
143
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(154 citation statements)
references
References 35 publications
7
143
0
4
Order By: Relevance
“…These unique amino acid alterations are reported to be associated with strains of S. tritici less sensitive to strobilurins and azoles. 23,24,26,27) The present assessment indicated that 2-acyl-5-methylisoxazolones were active against several fungi, including S. tritici. Referring to the preliminary results of the tests in vitro, we are planning in vivo evaluations of compounds exhibiting significant activity in parallel with the preparation of further variants of the isoxazol moiety.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…These unique amino acid alterations are reported to be associated with strains of S. tritici less sensitive to strobilurins and azoles. 23,24,26,27) The present assessment indicated that 2-acyl-5-methylisoxazolones were active against several fungi, including S. tritici. Referring to the preliminary results of the tests in vitro, we are planning in vivo evaluations of compounds exhibiting significant activity in parallel with the preparation of further variants of the isoxazol moiety.…”
mentioning
confidence: 60%
“…Recently, several strains less sensitive to strobilurin or azole products in some pathogens such as S. tritici have emerged. [20][21][22][23][24][25] There are some reports that amino acid alterations such as substitutions and deletions have been associated with strobilurin and azole resistance. In this study, amino acid alteration 143A in Cytochrome b, which is the target protein of strobilurin fungicides, has been identified in S. tritici.…”
mentioning
confidence: 99%
“…Examples of pathogens with increased virulence are the Ug99 pathotype of wheat stem rust (Singh et al 2008) and a new type of Puccinia striiformis (causal agent of stripe rust) adapted to warmer climates (Hovmøller et al 2008). A change in virulence may result from plant disease control methods as in the case of the rapid emergence and spread of QoI resistance in Mycosphaerella graminicola populations (Torriani et al 2009) or Puccinia triticina isolates able to overcome the resistance gene Lr9 (McCallum et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There have been concerted screens to develop new fungicides but, as in the pharmaceutical area, this has led to limited success. The strobolurin fungicides were successfully introduced and target the respiration pathway by inhibiting cytochrome bc1, but several plant pathogens have developed resistance reaching high levels [80]. The continued success of CYP51 inhibitors (also known as azole fungicides or demethylase inhibitors) has led to renewed interest in discovery of new agents also set against a backdrop of European regulation to improve the safety of pesticides.…”
Section: Food Security and Microbial Cytochromes P450mentioning
confidence: 99%